Why has Japan refused to apologise for the pacific war? - Low, James Han Kwang. (2010)
Memories of war elicit the most intense emotions in people as it is the nature of war and its circumstances that bring out the best and worst in us. Fifty years after the Pacific war, the memories of Japan's conduct in the Pacific War, and the atrocities perpetuated by its military continues to haunt those who experienced it. What many non-Japanese are unable to understand is the refusal of Japan to come to terms with its conduct of the war and its refusal to apologise unequivocally and sincerely to its victims, in spite of the overwhelming evidence. A refusal that had contributed to an atmosphere of distrust between the governments and peoples of East and South East Asia and Japan. This study is an attempt to answer that question. It attempts to examine the various arguments that had been advanced to explain Japan's refusal and categorised them into three perspectives. The first of these is the balance of power perspective that had come to characterise the conduct of the cold war. The study shows that the US in the pursuit of its policy of containment had reversed the course of political reforms started in Japan, immediately after the war. This reversal led to the reinstatement of the Japanese elite, tainted by war in order to quickly rebuild Japan as a "bulwark" of democracy against communism. The second perspective is a study of how the continuity of Japanese domestic and bureaucratic politics after the war conspired to make a rigorous examination of Japan's role in the war difficult. The last is the perspective of culture, the construct that has come to define Japanese uniqueness and character. The study shows that it is this construct of Japanese purity, innocence, virtue and superiority and embodiment of these values and beliefs in the imperial institution that makes a rigorous examination of its war time role difficult and unsettling for the Japanese.